2021
DOI: 10.1002/tesq.3055
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Optimal Mode of Input for the Acquisition of Formulaic Expressions

Abstract: BRIEF RESEARCH REPORTSTESOL Quarterly welcomes evaluative reviews of publications relevant to TESOL professionals. In addition to textbooks and reference materials, these include computer and video software, testing instruments, and other forums of nonprint materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Vu and Peters (2021b) suggest that the auditory input in reading‐while‐listening might include prosodic cues of collocations (Lin, 2012). Previous research has shown the role of auditory input in formulaic sequence acquisition (e.g., Lin, 2019, 2021). From a psychological perspective, auditory input may have a processing advantage over written input.…”
Section: Incidental Learning Of Collocations From Reading‐while‐liste...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vu and Peters (2021b) suggest that the auditory input in reading‐while‐listening might include prosodic cues of collocations (Lin, 2012). Previous research has shown the role of auditory input in formulaic sequence acquisition (e.g., Lin, 2019, 2021). From a psychological perspective, auditory input may have a processing advantage over written input.…”
Section: Incidental Learning Of Collocations From Reading‐while‐liste...mentioning
confidence: 99%
“…Written input, however, is indirectly processed because it must first be converted into a phonological code by subvocal naming before it is processed in working memory. Lin (2021) highlights the relevance of this working‐memory perspective for formulaic sequence research.…”
Section: Incidental Learning Of Collocations From Reading‐while‐liste...mentioning
confidence: 99%
“…Further improvements in the design and functions of IdiomsTube are needed, particularly in terms of deciding the priority level at which each FE is taught, distinguishing between the metaphorical and literal forms of FEs, and overcoming the problems arising from the lack of uniformity in user-uploaded English captions. These practical decisions should be informed by empirical research evidence, and these gaps are being filled through experiments in the lab as well as analyses of log files showing users’ in-app behaviours and patterns (see, e.g., Lin, 2021, under review, in preparation). Filling the empirical research gaps and tackling these technical challenges are crucial for IdiomsTube as well as all future automatic tools designed to facilitate independent English FE learning from any other video-streaming platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Although the speaking task and the spelling task are slightly less popular, they are important in terms of providing a variety of tasks through which learners may engage with different aspects of FE knowledge, including their phonological form, orthographic form, and composition. According to research in psycholinguistics on the role of the phonological loop in vocabulary learning (Baddeley, Gathercole & Papagno, 1998; see also Lin, 2021), engaging learners with the phonological form is particularly important for facilitating their memory of new vocabulary items. Some empirical studies found that learners who read new vocabulary aloud or silently in their heads seemed to remember the items more effectively than their counterparts who encountered the same vocabulary but were forbidden from reading the items aloud or silently (Baddeley et al, 1998).…”
Section: The Design Of the Consolidation Tasksmentioning
confidence: 99%
See 1 more Smart Citation